1991
DOI: 10.1175/1520-0450-30.7.973
|View full text |Cite
|
Sign up to set email alerts
|

Information Content of AVHRR Channels 4 and 5 with Respect to the Effective Radius of Cirrus Cloud Particles

Abstract: This paper investigates the important difference in the relationship between brightness temperatures between the 11-μm and the 12-μn AVHRR data and the microphysical properties of the semitransparent cirrus clouds. In the nonscattering approximation, the emittance for channels 4 and 5 are related through the absorption coefficient ratio that is the key parameter giving access to the size of cloud particles. The observed mean value of this parameter corresponds to effective radius of 18 μm for polydisperse sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(154 citation statements)
references
References 0 publications
3
137
0
2
Order By: Relevance
“…Parol et al (1991) showed similar β eff results for a small region of cirrus. Giraud et al (1997) developed an automated split-window analysis using these AVHRR channels that estimates a maximum value for β eff , using 21 AVHRR images of cirrus during fall over the northern Atlantic and Europe.…”
Section: Satellite Retrieval Of β Effsupporting
confidence: 61%
“…Parol et al (1991) showed similar β eff results for a small region of cirrus. Giraud et al (1997) developed an automated split-window analysis using these AVHRR channels that estimates a maximum value for β eff , using 21 AVHRR images of cirrus during fall over the northern Atlantic and Europe.…”
Section: Satellite Retrieval Of β Effsupporting
confidence: 61%
“…Two related algorithms are used to retrieve cloud products: the split-window technique (Inoue, 1985;Parol et al, 1991;Dubuisson et al, 2008) to retrieve the effective diameter and an algorithm similar to the IIR operational algorithm to retrieve the effective emissivity and the effective optical thickness.…”
Section: Retrieval Algorithms Of Cloud Parametersmentioning
confidence: 99%
“…In the thermal infrared atmospheric window (8-13 µm), cloud optical properties (optical thickness and ice crystal effective size) are retrieved using the split-window technique (SWT) (Inoue, 1985;Parol et al, 1991;Dubuisson et al, 2008). This method is generally limited to thin cirrus clouds (optical thickness less than approximately 3 at 12 µm) and small crystals (effective diameters smaller than approximately 40 µm).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies (Cooper et al, 2007;Cooper and Garrett, 2010;Wang et al, 2011) have shown that cirrus optical properties may be retrieved with a better accuracy using a combination of TIR channels instead of visible and near-infrared (VNIR) channels (such as the Nakajima and King method, Nakajima and King, 1990), as long as the cirrus is optically thin enough (with a visible optical thickness between roughly 0.5 and 3) and the CED is smaller than 40 µm. For example the split-window technique (Inoue, 1985) applied to the Advanced Very-High-Resolution Radiometer (AVHRR; Parol et al, 1991) and the Imaging Infrared Radiometer (IIR) onboard CALIPSO (Garnier et al, 2012(Garnier et al, , 2013) is used to retrieve CED and COT from the brightness temperature difference of two different channels in the infrared atmospheric windows where gaseous absorption is small. Based on the same spectral information, an optimal estimation method (OEM; Rodgers, 2000) is used for the Atmospheric Infrared Sounder V6 (AIRS, Kahn et al, 2014Kahn et al, , 2015) and in the research-level code of Wang et al (2016b, a) for MODIS.…”
Section: Introductionmentioning
confidence: 99%